Colonial Rewriting of African History: Misinterpretations and Distortions in Belcher and Kleiner’s Life and Struggles of Walatta Petros - Woldeyes, Yirga Gelaw (2020)
The Hagiography of Ethiopian Saint Woletta Petros was recently translated from Ge’ez into English by Wendy Belcher and Michael Kleiner. Belcher has no knowledge of Ge’ez and simple errors in the translation suggest that Kleiner lacks the fluency required to accurately interpret the language. A western lens with a deliberate distortion of the facts has been applied to the text, using contemporary western understandings of marriage and monastic life to interpret a 17th century Ethiopian nun. Contemporary ethnic politics have been inserted into the interpretation in a way that reproduces negative racial binaries, and relies heavily on the colonial racialization of African identities and western color prejudice that does not exist in Ethiopia. This has resulted in a colonial rewrite of one of Ethiopia’s most holy books. Belcher represents Woletta Petros as a violent, diseased and lustful nun, reproducing racist stereotypes about black women. Sexual scenes and a same-sex partnership between nuns have been inserted into the text where they do not exist in the Ge’ez original. This article will detail the most significant misinterpretations in Belcher and Kleiner’s translation. It will also offer an Ethiopian interpretation of Woletta Petros, considering her legacy within context and drawing on the testimony of the local scholars. The article will show that the translation, as well as Belcher’s subsequent publications around Woletta Petros, constitute colonial scholarship, where a foreigner who cannot understand the language is elevated to the status of expert at the expense of the local people who can not only read and write the language, but also have decadeslong training in the interpretation of these important holy texts. The article will demonstrate that the colonial practice of taking African intellectual resources and using them to rewrite African history is not a relic of the past, but an ongoing and supported practice within universities. Major universities, as important sites of knowledge production, should not contribute to racial prejudices and distortions of African history by supporting projects that are carried out by scholars who deliberately exclude or distort the voices and experiences of local people. This article seeks to prompt a change in the writing of African history, where the agency of black people to narrate their own histories and experiences is respected and supported.